Bruch’s Membrane Compartmentalizes Complement Regulation in the Eye with Implications for Therapeutic Design in Age-Related Macular Degeneration - Clark, Simon J.; McHarg, Selina; Tilakaratna, Viranga; Brace, Nicole; Bishop, Paul N. (Frontiers in Immunology, 2017)
Age-related macular degeneration (AMD) is the leading cause of blindness in the western world and affects nearly 200 million people globally. Local inflammation driven by complement system dysregulation is currently a therapeutic target. Bruch’s membrane (BrM) is a sheet of extracellular matrix that separates the retina from the underlying choroid, a highly vascularized layer that supplies oxygen and nutrition to the outer retina. Here we show that most complement proteins are unable to diffuse through BrM, although FHL-1, factor D and C5a can. AMD-associated lipid deposition in BrM decreases FHL-1 diffusion. We show that this impermeability of BrM creates two separate semi-independent compartments with respect to complement activation and regulation. Complement proteins synthesized locally on either side of BrM, or on the choroidal side if derived from the circulation, predominantly remain on their side of origin. As previous studies suggest that complement activation in AMD is confined to the choroidal side of BrM we propose a model whereby complement activation in the choriocapillaris layer of the choroid generates C5a, which crosses BrM to interact with its specific receptor on RPE cells to initiate an inflammatory response in the retina. Understanding mechanisms underpinning AMD is essential for developing therapeutics that target the right molecule in the right anatomical compartment.